IMPLEMENTASI KEBIJAKAN KODE ETIK JURNALISTIK DALAM PELIPUTAN BERITA MEDIA CETAK PADA BIRO HUMAS DAN PROTOKOL SETDA PROVINSI SULAWESI TENGAH - Yusuf, Muhammad (Katalogis, 2019)
The purpose of this research was to find out the officers’ performance at the Protocol and Travel Bureau of Public Relations and Protocol, Provincial Secretariat of Central Sulawesi. Performance is the result of quality and quantity of work accomplished by an officer in carrying out the jobs and responsibilities upon him. According to Robbins (2001: 187), there are 3 (three) aspects as a synergy of some positions: the head motivation, ability, and opportunity. This was qualitative research in which interactive analysis was employed. The informants were selected from some positions: the Head of Bureau, the Head of Section, the Head of Sub-section, and staff. Responsibility and mastery as well as the purpose of the research were criteria under consideration for selecting the informants. The research found the performance reflecting motivation and opportunity aspects at the Protocol and Travel Bureau has run well, but the mastery aspect has not. In current conditions, an organization needs to have human resources showing their specific qualification and professionalism, as well as good understanding relating to the protocol matters in governmental life in order to implement a performance-based staff management development.